Prevalence, risk factors and global impact of musculoskeletal injuries among endoscopists: a nationwide European study - Morais, Rui; Vilas-Boas, Filipe; Pereira, Pedro; Lopes, Pedro; Simões, Carolina; Dantas, Eduardo; Cunha, Inês; Roseira, Joana; Cortez-Pinto, João; Silva, João; Lage, Jorge; Caine, Mafalda; Rocha, Manuel; Flor de Lima, Margarida; Costa Santos, Maria Pia; Garrido, Mónica; Sousa, Paula; Marcos, Pedro; Azevedo, Richard; Castro, Rui; Cúrdia Gonçalves, Tiago; Leal, Tiago; Magno-Pereira, Vítor; Ramalho, Rosa; Rodrigues-Pinto, Eduardo; Macedo, Guilherme (Endoscopy International Open, 2020)
Background and study aims Previous studies have suggested a high prevalence of musculoskeletal injuries (MI) in endoscopists. Little evidence has come from European countries. Our main aim was to evaluate the prevalence, type, and impact of MI among Portuguese endoscopists. We also sought to identify risk factors for the development, severity and number of endoscopy-related MI.Material and methods A 48-question electronic survey was developed by a multidisciplinary group. The electronic survey was sent to all members of Portuguese Society of Gastroenterology (n = 705) during May 2019. Study data were collected and managed using REDCap electronic data capture tools hosted at SPG – CEREGA.Results The survey was completed by 171 endoscopists (response rate of 24.3 %), 55.0 % female with a median age of 36 years (range 26–78). The prevalence of at least one MI related to endoscopy was 69.6 % (n = 119), the most frequent being neck pain (30.4 %) and thumb pain (29.2 %). The median time for MI development was 6 years (range 2 months-30 years). Severe pain was reported by 19.3 %. Change in endoscopic technique was undertaken by 61.3 % and reduction in endoscopic caseload was undertaken by 22.7 %. Missing work was reported by 10.1 %, with the median time off from work being 30 days (range 1–90). Female gender and ≥ 15 years in practice were independently associated with MI and severe pain. Years in practice, weekly-time performing endoscopy, and gender were significant predictors of the number of MI.Conclusions Prevalence of MI was significant among Portuguese endoscopists and had a relevant impact on regular and professional activities.